Analysts, Macroeconomic News, and the Benefit of Active In-House Economists - Hugon, Artur; Kumar, Alok; Lin, An-Ping (The Accounting Review, 2016)
ABSTRACT Although macroeconomic news has a major impact on corporate earnings, anecdotal evidence suggests that financial analyst research is inefficient with respect to such news. Examining analysts' earnings research, we find that they underreact to negative macroeconomic news. Analysts are not all equal, though, as analysts employed at the same firm as an active macroeconomist underreact much less. We find that the benefit of analyst access to an economist is concentrated in firms that are high in cyclicality relative to their industry, high in cyclicality in general, and that are smaller in size. In addition, analysts who are exposed to more accurate or award-winning in-house macroeconomists benefit more. Investors appear to recognize the advantage of access to macroeconomists, reacting more strongly to these analysts' forecast revisions. Overall, our results suggest that the presence of an active in-house macroeconomist improves the efficiency and credibility of analyst research. JEL Classifications: G12; G14; G24